The Cloud and data sovereignty after Snowden - Vaile, David (Journal of Telecommunications and the Digital Economy, 2014)
The Snowden revelations have renewed interest in questions surrounding jurisdictional issues about where data is kept (location) and who claims the capacity to direct access to it be given by the entity hosting it (control). While early attitudes to the cluster of technologies marketed as The Cloud generally played down this aspect, and unilateral contracts offered by many major providers declined to specify these parameters for the technical provision of a Cloud service, growing appreciation that assurances of security and confidentiality are no barrier to certain forms of access being granted to third parties in other jurisdictions has rekindled interest. This paper explores the technical and legal issues involved from the perspective of an Australian business interested in both customer and government attitudes, and discusses how moves to implement jurisdiction location and control preferences have been characterised as Data Sovereignty and Digital Protectionism by differing interests.